The spirit of Marikana : the rise of insurgent trade unionism in South Africa - Sinwell, Luke (Wildcat (Pluto Press), 2016)
A comprehensive examination of the contemporary mineworkers' movement in South Africa, in a vivid ethnographic narrative.